Hubungan Pengetahuan dan Informasi terhadap Perilaku WUS pada Pemeriksaan IVA Test di Batu Intan Tahun 2024 - Shandy Kusumawardhani; Dira Saputri; Sitawati Sitawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Cervical cancer is one of the leading causes of death in women worldwide, generally caused by Human Papilloma Virus (HPV) infection. In Indonesia, this cancer ranks second as the most common type of cancer affecting women after breast cancer. Early detection through VIA (Visual Inspection with Acetic Acid) examination has been proven effective in reducing the risk of death from cervical cancer. However, the coverage of VIA examinations among women of childbearing age (WUS) is still relatively low. This study aims to determine the relationship between the level of knowledge and access to information on the behavior of WUS in conducting VIA examinations in Batu Intan Village, Girimaya District, Pangkalpinang City. This study used an observational analytical approach with a cross-sectional study design and involved 28 respondents of childbearing age women who met the inclusion criteria in 2024. The results of data analysis showed that there was a significant relationship between the level of knowledge and behavior in conducting VIA examinations with a significance value of p = 0.006, as well as a relationship between access to information and behavior with a significance value of p = 0.021. This indicates that the higher a person's knowledge about cervical cancer and the importance of early detection, as well as the better their access to health information, the more likely they are to participate in VIA screening. This study concludes that knowledge and access to information significantly influence the behavior of women of childbearing age in undergoing VIA screening. Therefore, interventions in the form of intensive education and the provision of easily accessible information need to be carried out continuously, both through health services, social media, and community outreach activities. Efforts to increase awareness and active participation in preventive screenings such as VIA testing are a strategic step in reducing the incidence and mortality from cervical cancer among women of childbearing age, especially in areas with limited screening coverage.